A tale of two groups: focusing on the differential vulnerability of "climate-induced" and "non-climate-induced" migrants in Dhaka City. (19th May 2018) - Adri, Neelopal; Simon, David
Abstract : Bangladesh is one of the most vulnerable countries in the world under the context of climate change. Each year thousands of migrants arrive in Dhaka City, the capital of the country, mainly forced by events such as floods, cyclone and riverbank erosion. Such group of migrants has been termed as "climate-induced" migrants in this research. The city also received other types of migrants who are not driven by climatic factors; rather their reasons for migration are purely opportunistic. This group has been termed as non-climate-induced migrants. The paper deals with the climate-induced and non-climate-induced migrants in Korail slum of Bangladesh who had arrived in Dhaka after 2006. This research attempted to analyse whether there are any differences in the characteristics, experiences and future aspiration between these two groups in spite of living in the same slum located in the capital of Bangladesh. Questionnaire survey, focus groups and key informant interview were the methods of data collection. Independent sample t -test and Chi-square test have been conducted to analyse data. Results revealed significant differences between the two groups in terms of income and savings, educational level, access to credit, contacts in the city, family structure, pattern of migration and relationship with the place of origin. The study revealed that if not properly planned, migration cannot be a suitable adaptation option.